How public policies and other events can shape spatial distribution of local activities over time? An investigation based on spatial micro-data. (February 2023) - Dubé, Jean; Dieng, Ousmane; Lévesque, Mathieu; Racine, Antoine; Roberge, Olivier; Trapé, Thibault
Abstract: The aim of the paper is to propose a methodological framework to explore how urban planning policies, such as the construction of highways, and other major events, such as opening/closure of major plants, affect the spatial distribution of residential and economic activities within a specific location over time. To do so, the paper proposes to use statistics related to the spatial distribution of individual buildings based on centrographic analysis, and to explore the statistical relations between the changes that occur over time with a vector autoregressive (VAR) model. From a land use policy perspective, this framework allows to investigate the causal impact of public action and other events on the local spatial distribution of the activities to see if (and how) it shapes spatial footprints and the distribution of residential and economic activities. The framework is applied to a small Canadian city case but can easily be implemented to any other cases. Highlights: A two-step model is developed to investigate causal relations à la Granger of spatial distribution of activities. The methodological framework is based on a micro-economic perspective. Construction of a highway have a causal influence on the spatial distribution of residential and economic activities. Closure of a major plant (paper mill) had an impact on the evolution of the spatial distribution of residential activities on the evolution of the spatial distribution of residential activities.